Effects of Red Fruit (Pandanus conoideus Lam) Oil on Malondialdehyde Level and Spermatozoa Quality in Mice (Mus musculus) Exposed to Monosodium Glutamate - Agustina, Widayati; Widjiati, Widjiati; Hayati, Alfiah (Folia Medica Indonesiana, 2018)
This study aimed to determine the effects of red fruit (Pandanus conoideus Lam) oil on MDA levels and spermatozoa quality in mice (Mus musculus) exposed to MSG. The quality includes motility, viability, concentration, and morphology of spermatozoa. This experimental study used randomized post-test only control group design. The subjects of this study were 25 mice (Mus musculus), divided into 5 groups (5 mice per group). K- group received distilled water for 35 days. K+ group received 4 mg/g BW MSG for 21 days. P1, P2, and P3 treatment groups received 4 mg/g BW MSG for 21 days and 0.02; 0.04; 0.08 ml/g BW red fruit oil, respectively, from day 22 to 35. The results showed that mean spermatozoa morphology in K-, K+, P1, P2, P3 groups were as follows: 0.86; 0.56; 0.67; 0.61; and 0.87 (%). The spermatozoa concentrations were sequentially as follows: 21; 10; 15; 32,8,19 (107 cells/ml). The spermatozoa's vitalities were as follows: 0,64; 0,14; 0,24; P2: 0.36; 0.68 (%). MDA levels were respectively: 0.29; 0.60; 0.35; 0.23; and 0.19 (nm). As a conclusion, testicular MDA levels in mice exposed to MSG and given with red fruit oil were lower than those in mice exposed to MSG without receiving red fruit oil. The quality of spermatozoa in mice exposed to MSG and receiving red fruit oil was higher than that of mice exposed to MSG without being given with red fruit oil.